(untitled) (Eureka Journal of Computing Science & Digital Innovation, 2026)
In Uzbekistan, bilingualism is growing quickly, especially among young English language learners. The phenomena of code-switching, or alternating between two or more languages in a same speech act, among Uzbek bilingual English learners is examined in this article. According to the study, learners regularly blend Uzbek and English idioms in everyday speech, which reflects sociocultural identification, motivation for language acquisition, and communicative effectiveness. The study demonstrates how code-switching functions as a learning method and a sign of bilingual competency by examining linguistic patterns and social attitudes.